The many facets of homeland security. - Laxminarayan, S.
This special issue on homeland security addresses some of the prime infrastructure and human engineering aspects; associated scientific research and development priorities; disease outbreak and consequence management technologies, including the psychological implications of terrorism, the ubiquitous information technology strategies that would take us through from data to information, to knowledge, intelligence and to wisdom; and the critical role of the United States Department of Homeland Security in coordinating all of these drastic changes and implementations in the continuing fight against all forms of terrorism, i.e, biological, chemical, nuclear/radiological, cyber, and so on.
Keywords: United States Department of Homeland Security; Bioterrorism; Consequence management technologies; Counterterrorism; Development priorities; Disease outbreak; Homeland security; Human engineering aspects; Information technology strategies; Infrastructure aspects; Psychological implications; Psychosocial impact